Dampak Pengangkatan Kembali Sri Mulyani Indrawati (SMI) Menjadi Menteri Keuangan Negara Republik Indonesia Terhadap Bursa Efek Indonesia (Event Study Pada Sektor Perbankan dan Real Estate) - Yuli Agustina (Akutansi Bisnis & Manajemen ( ABM ), 2016)
The purpose of this study was to see whether there is market reaction on the appointment of returning Sri Mulyani Indrawati (SMI) as Minister of Finance of Indonesia on July 27, 2016 as measured by abnormal return of the company. The population of this study were 92 companies comprising of the entire real estate sector companies as much as 49 and as many as 43 companies of the banking sector. Selection of the sample using purposive sampling which is a non-probability sampling technique by observing certain criteria in accordance with the purpose of research. The criteria in question is a company that has a stock price information as much as 51 days, consisting of 40 days as the estimation period, 5 days before the event, time of event and 5 days after the events announcement of the cabinet reshuffle vol 2, as well as a company that actively conduct sales transactions and purchase of shares (shares not sleep) during the event period. Study determined the final sample is 80 companies. While statistical tool used two different test paired samples (paired sample t-test) with the program PASW Statistics 18. The results obtained from this study showed a difference of capital market reaction before and after the event up again of SMI became finance minister of Indonesia measured abnormal return. At the company's real estate sector, there is a significant reaction obtained on a comparison of the second day before (H-2) with the second day after (H + 2) events, while in the banking sector companies significant reaction obtained on a comparison between the first day before (H -1) with the first day after (H + 1) after the event.